In vitro susceptibility to ceftazidime/avibactam and comparators in clinical isolates of enterobacterales from five Latin American Countries (2020)
Background: High rates of resistance to third-generation cephalosporins and carbapenems in Enterobacterales have been reported in Latin America. Ceftazidime/avibactam (CZA) is the combination of a third-generation cephalosporin and a non-β-lactam β-lactamase inhibitor, which has shown activity against isolates producing class A, C and D β-lactamases. Herein, we evaluated the activity of CZA and comparators against clinical isolates of Enterobacterales in Latin America. Methods: The activity of CZA and comparators was evaluated against clinical isolates of Enterobacterales from Argentina, Brazil, Chile, Colombia and Mexico that were collected between January 2016 and October 2017. One specific phenotypic subset was evaluated. A carbapenem non-susceptible (CNS) phenotype was defined as any isolate displaying a minimum inhibitory concentration (MIC) ≥1 mg/L for ertapenem. Results: CZA was active against 95.8% of all isolates and 77.5% of CNS isolates. Fosfomycin (FOS) and tigecycline (TGC) were the second most active antibiotics with 93.4% of Enterobacterales being susceptible. Conclusions: The results of this study underline the potential therapeutic role of CZA in Latin America.